PHP & MySQL novice to ninja - Butler, Tom (SitePoint, 2021)
PHP & MySQL: Novice to Ninja, 7th Edition is a hands-on guide to learning all the tools, principles, and techniques needed to build a professional web application using PHP & MySQL. Comprehensively updated to cover PHP 8 and modern best practice, this highly practical and fun book covers everything from installation through to creating a complete online content management system. Gain a thorough understanding of PHP syntax Master database design principles and SQL Write robust, maintainable, best practice code Build a working content management system (CMS) And much more!.
Previous edition: 2017. - Includes bibliographical references and index. - Description based on print version record
Keywords: MySQL (Electronic resource); PHP (Computer program language); Web site development; Database design; PHP (Langage de programmation); Sites Web; Développement; Bases de données; Conception